Pengaruh Beban Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan PT Perkebunan Nusantar IV Adolina Perbaungan - Supriana, Supriana; Suprayitno, Eddi; Elny, Sri (JRMB (Jurnal Riset Manajemen & Bisnis), 2022)
Performance (work achievement) is the result of work in terms of quality and quantity achieved by an employee in carrying out their duties in accordance with the responsibilities given. Research Objectives: To determine and analyze the influence of workload and work environment on employee performance at PT. Perkebunan Nusantara IV Adolina Perbaungan. The results of this research are simultaneous testing of the variables Workload (X1), Work Environment (X2) and Employee Performance (Y). Based on table 13 above, the calculated F value is 15,873 with a significance value of 0.000. From this data, because the F-calculated value (15,873) is above the F-table value (3.91), it can be concluded that the two independent variables, namely Work Load (X1) and Work Environment (X2) have a great influence on the dependent variable, namely Employee Performance. (Y) PT. Perkebunan Nusantara IV Adolina Perbaungan. Conclusion: Workload has a negative and significant effect on the performance of PT employees. Perkebunan Nusantara IV Adolina Perbaungan. The work environment is positive and significant for the performance of PT employees. Perkebunan Nusantara IV Adolina Perbaungan